Medicinal Plants and Isolated Molecules Demonstrating Immunomodulation Activity as Potential Alternative Therapies for Viral Diseases Including COVID-19 - Alhazmi, Hassan A.; Najmi, Asim; Javed, Sadique A.; Sultana, Shahnaz; Al Bratty, Mohammed; Makeen, Hafiz A.; Meraya, Abdulkarim M.; Ahsan, Waquar; Mohan, Syam; Taha, Manal M. E.; Khalid, Asaad (Frontiers in Immunology, 2021)
Plants have been extensively studied since ancient times and numerous important chemical constituents with tremendous therapeutic potential are identified. Attacks of microorganisms including viruses and bacteria can be counteracted with an efficient immune system and therefore, stimulation of body’s defense mechanism against infections has been proven to be an effective approach. Polysaccharides, terpenoids, flavonoids, alkaloids, glycosides, and lactones are the important phytochemicals, reported to be primarily responsible for immunomodulation activity of the plants. These phytochemicals may act as lead molecules for the development of safe and effective immunomodulators as potential remedies for the prevention and cure of viral diseases. Natural products are known to primarily modulate the immune system in nonspecific ways. A number of plant-based principles have been identified and isolated with potential immunomodulation activity which justify their use in traditional folklore medicine and can form the basis of further specified research. The aim of the current review is to describe and highlight the immunomodulation potential of certain plants along with their bioactive chemical constituents. Relevant literatures of recent years were searched from commonly employed scientific databases on the basis of their ethnopharmacological use. Most of the plants displaying considerable immunomodulation activity are summarized along with their possible mechanisms. These discussions shall hopefully elicit the attention of researchers and encourage further studies on these plant-based immunomodulation products as potential therapy for the management of infectious diseases, including viral ones such as COVID-19.